Therapeutic practice for manthaara kaasanr by indigenous medical practitioners in seleeted MOH areas in jaffna district and effectiveness of syrup vasaka peenisa oil thatisady churna/ suwasakudori pill - Vijayakumar, A. (University of Jaffna, 2016)
Indigenous and Allopathic Medical systems are the existing two health systems in Jaffna. Indigenous Medical Practitioners (IMPs) are carrying out treatment intended to relieve disorders through the Indigenous Medical System. Previous studies on Manthaara Kaasam (MK) and effectiveness of medicines has not been reported. Hence the aim of the research was to study the therapeutic practice for MK by IMPs and effectiveness of medicines. Manthaara Kaasam is a respiratory disease presenting with the main symptoms of sneezing, redness of nasal mucosa, running nose, chest pain and cough. It is caused by aggravation of Kapha dosha in cold environment during the rainy and cloudy climate. This study was carried out in two stages. Stage one was a cross sectional descriptive study which was done in 67 lMPs in 4 selected MOH areas in Jaffna District. Therapeutic practice for MK and the knowledge on it were identified from the IMPs in 1st stage of the study. Out of 67 IMPs, above 55% stated dew, drizzling and exposure to cold and cloudy climate causes the MK. Above 65% of the IMPs mentioned sneezing, cough, itching eye, expel out sputum, nasal irritation and running nose as the symptoms of MK. Of the total studied population (67), 88% (59) treated the MK subjects by examining their nadi. Among them 81% (48) diagnosed Vatha Kapha nadi. From the first stage of the study, two combinations of medicines were identified as the treatment of MK. They were syrup Vasaka, Thalisady churna and Peenisa oil (Combination I) and syrup Vasaka, Swasakudori pill and Peenisa oil (Combination II). The 2nd stage was a cross sectional observational study by observing the effectiveness of the two combinations of medicines. It was carried out in 150 MK subjects who were prescribed by two combinations separately (75subjects for each combination) for 15 days at Rural Ayurvedic Hospital, Kodikamam as per the inclusion and exclusion criteria. Subjects were examined on 5th, 10th, 15th, 25th, 35th and 45th days. Effectiveness of two treatment options were determined through the clinically relevant outcome indicators. The mean duration of days taken for the disappearance of symptoms completely was identified. The symptoms of itching eye, nasal irritation, pain in throat, nasal block and watering eyes disappeared within 7 to 11 days. Cough and expel out of sputum took 19 — 28 daysto disappear. From the results of the 2nd stage, it could be concluded that the two combinations ofmedicines were effective in Manthaara Kaasa disease.
Keywords: Manthaara kaasam; Therapeutic practice; Indigenous medical practitioners; Effectiveness; Medicines